2014
DOI: 10.1016/j.jbusres.2014.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of firm performance in emerging economies: Business groups, strategy, industry structure, and state support

Abstract: A rich literature has investigated the antecedents of firm performance in developed economies, resulting in a consensus view that firm resources and strategy are the key determinants. Several arguments, however, suggest that in emerging economies other factors are more important for firm performance. This study analyzes the impact of firm strategy and industry structure as well as business group membership and state support on firm performance in an advanced emerging economy, Turkey. Using a data set compiled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 58 publications
1
27
1
2
Order By: Relevance
“…Moreover, Samad et al [7] suggested that: (i) vision, mission, and goals in formulation strategy, and (ii) structure, strategy, and human resource aspects in implementation strategy, are profoundly related to the performance of organizations. A study by Karabag & Berggren [8], supported the influence of these strategies on organizational performance. Empirical evidence indicated that strategic planning appears as a practice to help improve the performance of non-profit organizational.…”
Section: Relationship Between Strategic Planning and Peformancementioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, Samad et al [7] suggested that: (i) vision, mission, and goals in formulation strategy, and (ii) structure, strategy, and human resource aspects in implementation strategy, are profoundly related to the performance of organizations. A study by Karabag & Berggren [8], supported the influence of these strategies on organizational performance. Empirical evidence indicated that strategic planning appears as a practice to help improve the performance of non-profit organizational.…”
Section: Relationship Between Strategic Planning and Peformancementioning
confidence: 95%
“…Even though abundant studies have been undertaken on this topic but the findings are inconclusive [8]. The mixed findings were due to several reasons.…”
Section: Moderating Effect Organizational Culture On the Relationshipmentioning
confidence: 99%
“…It has been unambiguously agreed that economic development is the basis for the development of a country's region because it affects social (first of all, employment) and other problems being resolved (Boggia & Cortina, 2010;Karabaga & Berggren, 2014;Kondyli, 2010;Silva & Ferreira-Lopes, 2014;Wu & Tam, 2015). In turn, the basis of the economic development lies in the industry.…”
Section: Proposed Methodology For Quantitative Assessment Of the Indumentioning
confidence: 99%
“…In other studies, various other indicators were observed. Sector impacts, sector concentration, product differentiation and stage of life cycle (Caloghirou, Protogerou, Spanos, & Papagiannakis, 2004); ownership structures, size, degrees of diversification and geographical location (Guerrini, Romano, & Campedelli, 2011); country effects (Goldszmidt, Brito, & de Vasconcelos, 2011); differences of government, trade policies, technology levels, internal competition and culture (Ketelhöhn & Quintanilla, 2012); firm strategy and the industry structure (Karabag & Berggren, 2014); market power and more efficient operation (Canarella, Miller, & Nourayi, 2013); lagged profitability, growth, productivity, firm age and industry affiliation (Yazdanfar, 2013) were used as indicators to explain the relationship with corporate profitability.…”
Section: The Relationship Between Profitability and Macroeconomic Indmentioning
confidence: 99%